How does tax progressivity and household heterogeneity affect Laffer curves? - Hans A. Holter; Dirk Krueger; Serhiy Stepanchuk (Goethe University Frankfurt, Center for Financial Studies (CFS), 2014)
How much additional tax revenue can the government generate by increasing labor income taxes? In this paper we provide a quantitative answer to this question, and study the importance of the progressivity of the tax schedule for the ability of the government to generate tax revenues. We develop a rich overlapping generations model featuring an explicit family structure, extensive and intensive margins of labor supply, endogenous accumulation of labor market experience as well as standard intertemporal consumption-savings choices in the presence of uninsurable idiosyncratic labor productivity risk. We calibrate the model to US macro, micro and tax data and characterize the labor income tax Laffer curve under the current choice of the progressivity of the labor income tax code as well as when varying progressivity. We find that more progressive labor income taxes significantly reduce tax revenues. For the US, converting to a flat tax code raises the peak of the Laffer curve by 6%, whereas converting to a tax system with progressivity similar to Denmark would lower the peak by 7%. We also show that, relative to a representative agent economy tax revenues are less sensitive to the progressivity of the tax code in our economy. This finding is due to the fact that labor supply of two earner households is less elastic (along the intensive margin) and the endogenous accumulation of labor market experience makes labor supply of females less elastic (around the extensive margin) to changes in tax progressivity.
urn:nbn:de:hebis:30:3-355715
Keywords: E62; H20; H60; 330; Progressive Taxation; Fiscal Policy; Laffer Curve; Government Debt